2021
DOI: 10.52547/rbmb.10.3.420
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Decitabine Effects on HDAC3 and HDAC7 mRNA Expression in NALM-6 and HL-60 Cancer Cell Lines

Abstract: Background: Decitabine is a potent anticancer hypomethylating agent and changes the gene expression through the gene's promoter demethylation and also independently from DNA demethylation. So, the present study was designed to distinguish whether Decitabine, in addition to inhibitory effects on DNA methyltransferase, can change HDAC3 and HDAC7 mRNA expression in NALM-6 and HL-60 cancer cell lines. Methods: HL-60, NALM-6, and normal cells were cultured, and the Decitabine treatment dose was obtained (1 µM) thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(36 reference statements)
1
0
0
Order By: Relevance
“…Indeed, Gemcitabine has broad anti-leukemic activity across different AML subtypes and is more effective than Ara-C, both in vitro and in vivo [ 52 ]. Our results are also in a good agreement with the preclinical studies, which indicated that Decitabine is a more effective anti-leukemic agent than 5-azacytidine [ 53 ], but five times less effective than Ara-C [ 54 ]. The mechanism of action of 5-azacytidine is different and involves primarily DNA hypomethylation.…”
Section: Resultssupporting
confidence: 90%
“…Indeed, Gemcitabine has broad anti-leukemic activity across different AML subtypes and is more effective than Ara-C, both in vitro and in vivo [ 52 ]. Our results are also in a good agreement with the preclinical studies, which indicated that Decitabine is a more effective anti-leukemic agent than 5-azacytidine [ 53 ], but five times less effective than Ara-C [ 54 ]. The mechanism of action of 5-azacytidine is different and involves primarily DNA hypomethylation.…”
Section: Resultssupporting
confidence: 90%